From Asian curiosity to eruptive American pest: Megacopta cribraria (Hemiptera: Plataspidae) and prospects for its biological control - Ruberson, John R.; Takasu, Keiji; Buntin, G. David; Eger, Joe E. Jr.; Gardner, Wayne A.; Greene, Jeremy K.; Jenkins, Tracie M.; Jones, Walker A.; Olson, Dawn M.; Roberts, Phillip M.; Suiter, Daniel R.; Toews, Michael D. (My University, 2013)
The kudzu bug or bean plataspid, Megacopta cribraria (Fabricius), is native to Asia where it appears to be widely distributed (although the taxonomy is not entirely clear), but is infrequently a pest of legumes. This bug appeared in 2009 in the southeastern United States, where it is closely associated with kudzu, Pueraria montana Lour. [Merr.] variety lobata [Willd.] Maesen & S. Almeida. However, the insect has become a consistent economic pest of soybeans, Glycine max (L.) Merr., and some other leguminous crops in areas where large numbers can build in kudzu, in addition to being a considerable nuisance in urban landscapes where kudzu occurs. The insect has remarkable capacity for movement, and has spread rapidly from nine Georgia counties in 2009 to seven states in 2012. Despite being a nuisance in urban areas and a crop pest, high populations of the bug also reduce the biomass of kudzu, which is itself a seriously problematic invasive weed, complicating the status of M. cribraria in its expanded range. Extant predators and a pathogen in the US have been observed attacking kudzu bugs in the laboratory and field, but no parasitism of eggs or nymphs has been observed to date. A single record of parasitism of an adult kudzu bug by a tachinid fly is known from the US, but no other adult parasitism has been observed in the US or elsewhere. Extant enemies may eventually significantly reduce the bug’s populations, but at present native enemies appear to be insufficient for the task, and exotic enemies from the kudzu bug’s native range may offer the best possibility for effective biological control in the US. Based on the available literature, the best option for an importation biological control program appears to be the platygastrid egg parasitoid Paratelenomus saccharalis (Dodd) because of its apparent host specificity, intimate biological linkages with M. cribraria, and wide geographic distribution in the Eastern Hemisphere. Other natural enemies may eventually emerge as good candidates for importation, but at present P. saccharalis appears to be most promising.
Citation: Ruberson, J. R., Takasu, K., Buntin, G. D., Eger, J. E., Gardner, W. A., Greene, J. K., ... Toews, M. D. (2013). From Asian curiosity to eruptive American pest: Megacopta cribraria (Hemiptera: Plataspidae) and prospects for its biological control. Retrieved from http://krex/ksu/edu
Keywords: Kudzu bug; Bean plataspid; Globular stink bug; Biological control; Invasive species